Environmental monitoring - Wiersma, G B (CRC Press, 2015)
Focusing on pollution issues and impacts resulting from human activities, this book brings together conceptual basis behind the complex and specific approaches to the monitoring of air, water, and land. It addresses legislative focus on high-quality data results and conducting monitoring programs in different ecosystems and environmental media.